Enhancements to commissioning techniques and quality assurance of brachytherapy treatment planning systems that use model-based dose calculation algorithmsa - Rivard, Mark J.; Beaulieu, Luc; Mourtada, Firas (Medical physics (Lancaster), 2010)
The current standard for brachytherapy dose calculations is based on the AAPM TG-43 formalism. Simplifications used in the TG-43 formalism have been challenged by many publications over the past decade. With the continuous increase in computing power, approaches based on fundamental physics processes or physics models such as the linear-Boltzmann transport equation are now applicable in a clinical setting. Thus, model-based dose calculation algorithms (MBDCAs) have been introduced to address TG-43 limitations for brachytherapy. The MBDCA approach results in a paradigm shift, which will require a concerted effort to integrate them properly into the radiation therapy community. MBDCA will improve treatment planning relative to the implementation of the traditional TG-43 formalism by accounting for individualized, patient-specific radiation scatter conditions, and the radiological effect of material heterogeneities differing from water. A snapshot of the current status of MBDCA and AAPM Task Group reports related to the subject of QA recommendations for brachytherapy treatment planning is presented. Some simplified Monte Carlo simulation results are also presented to delineate the effects MBDCA are called to account for and facilitate the discussion on suggestions for (i) new QA standards to augment current societal recommendations, (ii) consideration of dose specification such as dose to medium in medium, collisional kerma to medium in medium, or collisional kerma to water in medium, and (iii) infrastructure needed to uniformly introduce these new algorithms. Suggestions in this Vision 20/20 article may serve as a basis for developing future standards to be recommended by professional societies such as the AAPM, ESTRO, and ABS toward providing consistent clinical implementation throughout the brachytherapy community and rigorous quality management of MBDCA-based treatment planning systems.